(untitled) (Nordic Journal of African Studies, 2000)
After a historical overview of reforms in teacher training since independence in 1960, this article goes on to discuss the problems today, through fieldwork carried out in 1998 in Ségou and Mopti, the two sites chosen by this NUFU project. The article analyses the situation from the viewpoint of active teachers, retired teachers, school directors and pedagogical counsellors. The questionnaires show that the different parties find that the initial training is not adapted to today’s needs, especially with respect to pedagogical innovations like convergent pedagogy. Such reforms are taught only in summer courses. Though this is necessary for teachers already in practice, new methods should be included in the initial training and at the same time supplementary education should not limit itself to the latest reforms, but reinforce and improve the teachers’ pedagogical practice. Furthermore, there should be special training for teachers in schools for teachers.